Serum level of IL-37 as a modulator in atherosclerosis, correlating its levels with oxidative stress and disease progression - A. H. A. A. Khan; E. A. H. Al-Alwany; R. S. A. Al-Azawi; J. G. A. Al-Jebori; S. M. Alkafagy; S. S. A. Al-Khakani; H. H. K. Al-Shukri; A. S. Abdulhasan (Regulatory Mechanisms in Biosystems, 2025)
Atherosclerosis is a disease where fat, fibrous materials, and calcium build up in the large arteries. This harmful process starts when the inner lining of blood vessels becomes active. This leads to a chain of reactions that cause the blood vessels to narrow and trigger inflammation, eventually resulting in the formation of fatty deposits called atheromatous plaques. Together, these related processes lead to heart problems, which are the main cause of death around the world. T he aim o f this research is to elucidate the function of IL-37 as a modulator in the pathophysiology of atherosclerosis through an examination of its ass o ciation with oxidative stress and the advancement of the disease. This case-control investigation endeavors to quantify IL-37 concentrations in individuals diagnosed with atherosclerosis in comparison to healthy control subjects, thereby evaluating its viability as a biomarker indicative of disease severity and its correlation with markers of oxidative stress. This investigation encompassed a cohort of 50 individuals receiving treatment at the Al-Najaf Center for Cardiac Surgery and Catheter Interve n tion located in Al-Najaf Province, Iraq. A volume of 5 mL of venous blood was procured from each participant, with serum being promptly isolated and subsequently preserved at – 80 °C. The concentrations of serum IL37 and TNF-α were quantified employing a human IL37 & TNF-α ELISA kit. The findings demonstrated that, in comparison to control, atherosclerosis p a tients had significantly higher levels of biochemical variables such as CK-MB, Trop I, MDA, Ox-LDL, and hs-CRP. IL37 and TNF-α mean values showed that patients' levels of IL37 were significantly lower than those of the control group, while TNF-α levels were significantly higher. According to Pea rson correlation, there was a significant negative connection between IL37 and TNF-a, MDA, Ox-LDL, RBS, TC, LDL, urea, CK-MB, TropI, and hs-CRP, whereas there was a negative nonsignificant correlation between IL37 and TG and creatinine. In conclusion, research on the function of IL-37 as a modulator in atheroscl e rosis has shown significant relationships between oxidative stress, IL-37 levels, and the development of the disease.